A 2D covalent organic framework as a high-performance cathode material for lithium-ion batteries. (April 2020) - Wu, Manman; Zhao, Yang; Sun, Binqiao; Sun, Zhenhe; Li, Chenxi; Han, Yu; Xu, Lingqun; Ge, Zhen; Ren, Yuxin; Zhang, Mingtao; Zhang, Qiang; Lu, Yan; et al.
Abstract: Organic cathode materials for lithium storage have attracted wide attention owing to their very diverse structures and largely tuned engineered molecular levels. However, it remains a great challenge to design a cathode material with simultaneously combined features of high specific capacity, cycle life and rate performance. Here, based on our proposed strategy, we design and report a BQ1-COF consisting of maximum active groups (C=O and C=N) with minimal inactive groups, which when used as cathode materials for lithium-ion batteries give a reversible capacity of 502.4 mA h g −1 at 0.05C, so far the highest capacity among polymer-based cathode materials. More importantly, the stable framework structure delivers an excellent capacity retention (81% after 1, 000 cycles at 1.54 A g −1 ), and it is noted that the rate performance (170.7 mA h g −1 even at 7.73 A g −1 ) is far superior to previous related reports. These results indicate that maximizing the loading of redox active groups in a stable network structure is an effective strategy to design organic cathode materials simultaneously with high capacity and outstanding cycle and rate performance for next generation lithium-ion batteries. Graphical abstract: Image 1 Highlights: A strategy for the design of LIB cathode materials with overall high performance is proposed. BQ1-COF delivers the highest capacity among polymer-based cathode materials so far in literatures. The stable structure of BQ1-COF affords an excellent cycle performance. The rate performance (170.7 mA h g −1 even at 7.73 A g −1 ) is far superior to previous related reports.